2015
DOI: 10.1177/0305735614567701
|View full text |Cite
|
Sign up to set email alerts
|

Music in radio advertising: Effects on radio spokesperson credibility and advertising effectiveness

Abstract: The widespread use of music in advertising derives from the belief among advertisers that music confers a significant commercial advantage; music has also aroused interest among researchers trying to determine its potential to add value and enhance advertising effectiveness. So, this article analyses the influence of music and congruency with the radio advertising message on spokesperson’s credibility and advertising effectiveness. We designed radio programs in which an ad hoc radio spot was inserted into a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…Consistent with numerous past studies, this study demonstrated that even though consumers liked music itself, which is not necessarily positive in terms of advertising music. Many studies have suggested that music can improve the effectiveness of advertising if it is congruent with the advertiser's message (e.g., Kellaris et al., ; Martín‐Santana et al., ). Kellaris et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with numerous past studies, this study demonstrated that even though consumers liked music itself, which is not necessarily positive in terms of advertising music. Many studies have suggested that music can improve the effectiveness of advertising if it is congruent with the advertiser's message (e.g., Kellaris et al., ; Martín‐Santana et al., ). Kellaris et al.…”
Section: Discussionmentioning
confidence: 99%
“…Music is most often applied for in‐store marketing and advertising. Research has indicated that music plays a crucial role in advertising at the cognitive (attracting attention and enhancing recall), affective (improving attitude toward the advertising/brand), and behavioral (changing behavior) levels (Alpert & Alpert, ; Martín‐Santana et al., ; Zander, ). However, most advertising studies exploring the effects of music have lacked an in‐depth understanding of music psychology when choosing their music.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion of using an experimental audio-visual stimulus alone was also not sufficient for inclusion in the present review. The semantic function of music in persuasive communication in advertising (e.g., Hung, 2000, 2001; Martín-Santana, Reinares-Lara, & Muela-Molina, 2015; Zhu & Meyers-Levy, 2005; Ziv, Hoftman, & Geyer, 2011) or in reporting of news (e.g., Kopiez, Platz, & Wolf, 2013) is not easily equated with the function of music in fictional film due to different reception mechanisms in these fundamentally different media formats. Studies on music’s potential to convey meaning in video games (e.g., Lipscomb & Zehnder, 2004) were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of voice to these professional voice users (PVUs), 1 it may be presumed that their occupational effectiveness is increased by the use of a "good" voice, that is, a voice that meets their individual needs in terms of stamina, power, intelligibility, and the ability to convey specific moods and attitudes or be perceived positively by listeners. [2][3][4] Good voice quality can also have personal advantages, such as greater vocal attractiveness, 5,6 credibility, 7 and a positive association with desirable personality attributes. 8,9 Good voice quality thus appears to have both occupational and personal advantages; it is likely to be a useful communicative attribute for PVUs in many aspects of their lives.…”
Section: Introductionmentioning
confidence: 99%